(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
New fluorine-containing chiral auxiliary (S)-N-(2-benzoyl-phenyl)-1-(2- fluorobenzyl)pyrolidyne-2-carboxamide ((S)-2-FBPB) and its plane-square Ni(II) complex of Shiff base with serine is synthesized. The synthesis of chiral auxiliary has been carried out in the presence of CH2Cl2 at 0 oC via condensation of 2-aminobenzophenone with 2-fluorobenzylproline, through intermediate formation of chloranhydride in the presence of PCl5. The synthesis was carried out in CH3OH in the presense of strong base (KOH). As expected during the synthesis of the serine complex with new fluorine-containing chiral auxiliary (S)-2-FBPB of diastereoizomeric complexes (S,R)/(S,S) in a ratio 99/1 has been derived.